2022
DOI: 10.3390/curroncol29120737
|View full text |Cite
|
Sign up to set email alerts
|

Controlateral Symmetrisation in SRM for Breast Cancer: Now or Then? Immediate versus Delayed Symmetrisation in a Two-Stage Breast Reconstruction

Abstract: Introduction: The timing of contralateral symmetrisation in patients with large and ptotic breasts undergoing a unilateral skin-reducing mastectomy (SRM) is one of the most debated topics in the reconstructive field. There is no evidence to support the advantage of immediate or delayed symmetrisation to help surgeons with this decision. The aim of this study was to investigate the clinical and aesthetic outcomes of immediate symmetrisation. Methods: A randomised observational study was conducted on patients wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…The patient returned for an early postoperative check one week later, showing good clinical conditions. Signs of ischemic suffering of both NACs were evident, while the inframammary wound was in a satisfactory state after an appropriate wound-care and management of NAC’s skin necrosis [ 36 , 37 , 38 , 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…The patient returned for an early postoperative check one week later, showing good clinical conditions. Signs of ischemic suffering of both NACs were evident, while the inframammary wound was in a satisfactory state after an appropriate wound-care and management of NAC’s skin necrosis [ 36 , 37 , 38 , 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Casella et al showed that all BREAST-Q domains were higher in the immediate balancing group, but only satisfaction with the breast score was significantly higher in the immediate group than in the delayed group (P < 0.05). 20 Rancati et al found similar outcomes in both groups concerning BREAST-Q and SF-36 parameters, with no significant differences, except for psychosocial well-being, which was higher in the immediate group. 21 Laporta et al used a modified grading scale originally described by Cohen et al, with a high score for the general satisfaction subitems without a significant difference between the immediate and delayed groups.…”
Section: Satisfaction Levelmentioning
confidence: 89%
“…[23][24][25] Three studies did not mention the specific complications, and two did not mention the complication rate. [20][21][22]26,27 Four of five studies included immediate cases alone without comparisons with delayed symmetrization. Two studies did not report any major complications, 29,30 with only one case of complications (0.98%) in the third study.…”
Section: Complications Ratementioning
confidence: 99%
“…Traditionally, implant placements include submuscular [83][84][85] and subglandular placement. 86,87 An epidemiological study reports CC incidence rates of 1.9% and 9.6%, respectively.…”
Section: Breast Implant Placementsmentioning
confidence: 99%